The Role of Apelin in Cardiovascular Diseases, Obesity and Cancer - Wysocka, Marta B.; Pietraszek-Gremplewicz, Katarzyna; Nowak, Dorota (Frontiers in Physiology, 2018)
Apelin is an endogenous peptide identified as a ligand of the G protein-coupled receptor APJ. Apelin belongs to the family of adipokines, which are bioactive mediators released by adipose tissue. Extensive tissue distribution of apelin and its receptor suggests, that it could be involved in many physiological processes including regulation of blood pressure, body fluid homeostasis, endocrine stress response, cardiac contractility, angiogenesis and energy metabolism. Additionally, this peptide participates in pathological processes, such as heart failure, obesity, diabetes and cancer. In this article, we review current knowledge about the role of apelin in organ and tissue pathologies. We also summarize the mechanisms by which apelin and its receptor mediate the regulation of physiological and pathological processes. Moreover, we put forward an indication of apelin as a biomarker predicting cardiac diseases and various types of cancer. A better understanding of the function of apelin and its receptor in pathologies might lead to the development of new medical compounds.